Detail specification for multi-contact circular electrical connectors for d.c. and low frequency applications. Bayonet couplingnon-barrier sealed, environment resistant with rear insertable, rear release, rear removable crimp contacts also barrier sealedwith non-removable solder contact styles. Full plus airframe fit assessment. (15th October 1990) - British Standards Institution,
No abstract available